Strengthening the Monetary Policy Framework in Korea - Clinton, Kevin; Craig, R.; Laxton, Douglas; Wang, Hou. (Washington, D.C. : International Monetary Fund, 2019)
Adoption of inflation targeting by the Bank of Korea (BOK) in 1998 contributed to low and stable inflation. However, after the global financial crisis (GFC) monetary policy faced more challenging conditions. Inflation slipped below the target range in 2012 and remains below it despite a cut in the target to 2 percent in 2016. Policy also became more complex with the addition of financial stability to the central bank's mandate. To address these challenges, this paper proposes a two-pronged approach to strengthen the effectiveness with which monetary policy can meet its objectives: first, enhanced communication on how the target will be achieved over the medium-term, building on a forecasting and policy analysis system; and, second, by clarifying the complementary role of macroprudential policy in containing financial stability risks so that monetary policy can focus on the inflation target. Simulation of a macro model calibrated to Korea illustrates how it can be used to provide this greater medium-term focus on achieving the inflation target and strengthen communication.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet